Predicting Cyberspace Addiction Based on Marital Intimacy and Self-worth and Life Quality in Married Women - Faramarzi, Salar; Ajalloueian, Nafiseh; Ghasemi, Simin (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Prevention is better than treatment in any field, therefore numerus pathologists believed that the root of many abnormal behaviors and effective factors on them must be identified specially internet addiction which is a new phenomenon. The aim of present research was to predict cyberspace addiction based on marital intimacy, self-worth and life quality of married women living in Isfahan City. Methods: The present study was a descriptive correlational study. Research population were including 270 married women leaving in Isfahan city based on convenient sampling method. They were selected and participated into the research in fall of 2022. Data collection instrument were consisted of marital intimacy questionnaire of Thompson and Walker (1983), the self-worth questionnaire of Doosti and Hoseininia (2021), the life quality questionnaire of World Health Organization, Cyberspace addiction’s questionnaire of Young (1998). They were implemented online via virtual environment. The achieved data were analyzed by stepwise regression statistical method using SPSS software version 24. Results: The results showed that Self-worth (B = -0.549), quality of life (B = -0.446) and marital intimacy (B = -0.107) were able to predict 16.7% of cyberspace addiction. Conclusion: As a result of the findings of the present study, it can be inferred that self-worth, quality life quality and marital intimacy play an important role in preventing cyberspace addiction. In other word, the higher self-worth, quality of life and marital intimacy, resulted in the lower cyberspace addiction.